The colour of risk: an exploration of the IPCC's 'burning embers' diagram - Mahony, Martin; Hulme, Mike (University of Toronto Press, 2012)
This article tracks the historical emergence of a new visual convention in the representation of the risks associated with climate change. The “reasons for concern” or “burning embers” diagram has become a prominent visual element of the climate change debate. By drawing on a number of cultural resources, the image has gained a level of discursive power which has resulted both in material mobility and epistemic transformation as the diagram itself has become a tool for a variety of actors to reason with. The case brings to light a number of challenges associated with attempts to know and visualize abstract concepts such as risk and danger, including the social organisation of knowledge production and the role of expert judgment in contexts where science is asked to retreat from normativity.